Unionist Voices and the Politics of Remembering the Past in Northern Ireland - Simpson, Kirk. author. aut Link
X, 176 p.
Keywords: Simpson offers a reflective and theoretical explanation of the ways in which unionists conceive of the past in the present post-conflict environment. He considers the ways in which scholarly literature has often painted an outdated and inaccurate portrait of a highly complex people.